Women's political movements in the West Bank and Israel: challenging perspectives from within - Daniele, G. (Fe Dergi: Feminist Elextiri, 2013)
In the context of the Israeli-Palestinian conflict, the role played by women activists in overcoming exclusivist ethno-national narrative identities by means of feminist as well as peace-oriented perspectives represents a central issue within grassroots activism and academia. In particular, the paper focuses on the main initiatives experienced by Palestinian and Israeli Jewish women in both their own societies and joint projects, such as the most well known, Jerusalem Link. Nevertheless, the current reality reveals controversial obstacles to contextualise these alternative political actions with the aim of suggesting feasible conflict resolutions. Although women activists have attempted to build egalitarian and dialogical relationships across conflicting narratives, in the last decade the majority of such instances have continued to produce internal asymmetries between the “occupier” and the “occupied”, without achieving a common proposal to end the Israeli military occupation, and, as a consequence, a just resolution of the conflict.